THE MAKING OF ENGLISH CROSSWORD PUZZLE BOOK FOR VOCABULARY LEARNING FOR JUNIOR HIGH SCHOOL STUDENTS - Jamatul Khairiah; Rionaldi Rionaldi; Aprizawati Aprizawati (Politeknik Negeri Bengkalis, 2017)
Abstract : Vocabulary is one of important elements to be mastered In learning a foreign language. However, in real condition, the students sometimes feel bored and less interested to learn vocabulary. The aimed of this study was to make a Crossword Puzzle Book to help students to learn English vocabulary. It was designed to help students to be more interested in learning vocabulary. There were several processes in making the book, started from collecting the material, designing and printing the book. The application used was Photoshop and Microsoft Office Excel. The source materials of the book were taken from several sources. They were English text book, dictionary and Internet. The arrangement of the content is thematic. Interesting topics were chosen and several images were added. Besides, there are 4 question types: Synonym, Antonym, Question based on image, and Description. This book provides students a review course material, so that, it is expected to help students in learning vocabulary and remember it easily.